English, asked by aryanmasih825, 6 months ago

(x+6) (x-10) solve by using identity..

❌❌❌no spamm..

yaar plz solve it...............☹​

Answers

Answered by Anonymous
8

( x - 6 ) ( x + 10 )

x^2 + 10x - 6x - 60 { x^2 means x square }

x^ 2 + 4x - 60

Answered by Anonymous
3

Answer:

Answer: Given,

(

x

+

4

)

(

x

+

10

)

We know that,

(

x

+

a

)

(

x

+

b

)

=

x

2

+

(

a

+

b

)

x

+

a

b

Here, a = 4 and b = 10

Therefore,

(

x

+

4

)

(

x

+

10

)

=

x

2

+

(

4

+

10

)

x

+

4

×

10

=

x

2

+

14

x

+

40

Answer

Explanation:

question puch raha hay ki udas hay ????

Similar questions